Haematological and biochemical profile of Mecheri sheep during winter and summer - SELVARAJ, P; MATHIVANAN, R; NANJAPPAN, K (The Indian Journal of Animal Sciences, 2014)
Influence of seasonal effect on hemato-biochemical parameters of Mecheri sheep was studied. No change in hematological values of RBC, WBC, Hb and ESR were observed during winter between preweaning, postweaning, 1-2 years and adult groups except for PCV. pev values were significantly (P<0.05) higher in adult animals in winter compared to other groups. However, RBC levels were significantly higher in preweaning and in adult male compared to other groups during summer. Similarly, PCV (%) values were higher in preweaning compared to postweaning group and males of 1-2 years and adult group had higher pev than females of the respective group. There was no significant variation in serum glucose, total protein and albumin concentrations in all the groups during both the seasons. However, total cholesterol content increased significantly as age advanced during both the seasons. Similarly, HDL concentrations were lower in preweaning and postweaning groups compared to 1-2 years and adult groups in both the seasons.